Polypyrimidine tract binding protein knockdown reverses depression-like behaviors and cognition impairment in mice with lesioned cholinergic neurons - Zhou, Yiying; Zhang, Ke; Wang, Fangmin; Chen, Jiali; Chen, Shanshan; Wu, Manqing; Lai, Miaojun; Zhang, Yisheng; Zhou, Wenhua (Frontiers in Aging Neuroscience, 2023)
Depression is a common comorbidity of dementia and may be a risk factor for dementia. Accumulating evidence has suggested that the cholinergic system plays a central role in dementia and depression, and the loss of cholinergic neurons is associated with memory decline in aging and Alzheimer's patients. A specific loss of cholinergic neurons in the horizontal limb of the diagonal band of Broca (HDB), which is an innervation of the hippocampal formation, is correlated with depression and dysfunction of cognition in mice. Recently, astrocytes can transform were reprogrammed into functional neurons by depleting the RNA-binding protein polypyrimidine tract binding protein (PTB; also known as PTBP1). Here, we report the conversion of astrocytes to newborn cholinergic neurons by depleting PTB in HDB. First, the loss of cholinergic neurons was induced by injection of 192 IgG-saporin into HDB; then, we examined whether depletion of PTB using either antisense oligonucleotides or adeno-associated virus-shRNA (GFAP promoter) into the injured area of HDB could specifically transform astrocytes into cholinergic neurons and reverse depression-like behaviors and cognition impairment. We found that knockdown of PTB by both approaches could replenish newborn cholinergic neurons in the injured area of HDB, relieve the depression-like behaviors, and protect against alleviate cognitive impairment in mice with lesioned cholinergic neurons. In conclusion, these findings suggest that supplementing cholinergic neurons after PTB knockdown may be a promising therapeutic strategy to revert depression-like behaviors and cognitive impairment.